PHENOMENON OF ELASTICITY OF THE ACADEMIC YEARS AT THE UNIVERSITY OF BANDUNDU FROM 2019 TO 2020 - Antoine, MOMELA LISOMA; Ignace, MUPA ISANSAKA; Gédéon, SANTINI ELEWA (IJRDO-Journal of Applied Science, 2022)
The university is considered a high place of knowledge scientific, training senior executives, designing ideas that can move a country forward (EKWA BISISAL 2004). And yet the duration of an academic year is fixed by the State which has the organizational power of national education. This duration is fixed at thirty weeks of effective teaching subdivided into two semesters of fifteen weeks each. At the start of each academic year, the Minister of higher and university education continues to draw attention by instruction to the heads of establishments in its sector on respecting the academic calendar in order to avoid the elasticity of the academic years. But a good number of institutions of higher education and universities in the Democratic Republic of Congo, in this case the University of Bandundu, often experience disruptions in the application of the academic calendar as planned by the supervisory ministry. Some institutions, even faculties or sections take more than ten months to complete the full program of an academic year and others go beyond twelve months to complete the academic activities. Reason why we would like to know: What are the factors that disrupt teaching at the University of Bandundu? In other words, does the management committee properly manage academic fees? This situation constitutes a handicap on the level of training of the students.